Best practice in management persuasive communication of palace writer in the diplomatic letter - Noor Muhammad, Salmah Jan; Nik Muhamad Affendi, Nik Rafidah; Che Rodi, Rozita (Mattingley Publishing, 2020)
A palace writer or secretary to a king is the person responsible for authoring his official letter. These people have the intelligence in the field of writing or writing and have a close relationship with the king. Hence, the advantage that it has made it easier to write letters according to the aim that required by his king, especially in diplomatic relations. Among the methods applied by the palace writers through letters are persuasive communication. This persuasive communication is important to influence other governments in establishing diplomatic relations or resolving conflicts that arise. This study will identify and analyze the persuasive communication applied by palace writers through diplomatic letters sent to other governments. In addition, this research method will use the library method and research data analysis. The findings show that this persuasive communication is among the best methods used by palace writers in diplomatic correspondence sent to the affected government. This study will directly contribute to persuasive communication research and also highlight the role of the palace writers as well as studies on the diplomatic correspondence of the Malay sultanate.